Kolaborasi Mahasiswa Dalam Pembangunan Agrowisata Di Kelompok Wanita Tani Garuda 12 Cipayung Kecamatan Ciputat - Amalia, Fisy; Saefullah, Aep; Yolita, Reva Putri; Rumua, Yasir; Yuliansyah, Muhammad Fadly; Khaila, Putri; Nurhidayat, Muhamad; Pratama, Kelvin Putra; Putri, Amelia Meisya; Rahmadini, Amelia Suci; Syahrani, Elvira; Lestari, Wiwin; Syafirlah, Ambar; Hamid, Abdul; Hafidz, Abdul; Aini, Emizatul (LPPM STIE Ganesha, 2024)
Community service conducted by students plays a crucial role in the development of agrotourism, which combines the agricultural sector with tourism to enhance economic and educational value in rural areas. Students from the Ganesha School of Economics collaborated with the Tangerang Selatan Regional Government in developing agrotourism at the Kelompok Wanita Tani (KWT) Garuda PPM 12, in Cipayung, Ciputat, in April 2024. With an area of approximately 2000 m², which is a public facility in the Pondok Payung Mas Residence, this program aims to increase economic capacity and environmental conservation through training and appropriate technology. Challenges in agrotourism development, such as limited resources and market access, can be overcome by enhancing human resource capacity, utilizing technology, and fostering collaboration between the government, industry, academia, and the community. Students contribute through research, education, and mentoring, which help increase productivity, efficiency, and the appeal of agrotourism destinations. The methods of implementation include training and direct field assistance. The positive impacts of this program include local economic improvement, environmental conservation, community empowerment, and strengthening cultural identity. Student involvement in community service in the field of agrotourism not only brings economic benefits but also builds better environmental and cultural awareness